Quantitative Description of the Hindwings of the Different Populations of the Rice Black Bug Scotinophara Coarctata using Landmark-based Geometric Morphometrics (Journal of Informatics and Mathematical Sciences, 2017)
Due to pest outbreaks, rice production has been decreasing all these years. The rice black bug (RBB), Scotinophara coarctata has recently been considered to be a major problem of rice producing regions in the Philippines especially in Mindanao. Since there were observations that the patterns of infestations of rice plants vary between ricefields in different geographical areas, it was hypothesized that populations of the pest vary. To be able to understand these differences observed, morphological shape variations of hindwings in RBB were quantified and determined using landmark-based geometric morphometrics. Results revealed within population variations due to sexual dimorphism. Significant differences between non-outbreak and outbreak populations and between geographically different populations were also observed although the differences were not based on distances between populations. The results indicate that the differences could be attributed to the distinctness of each of the populations examined and could be due to selection of selected genotypes that are able to survive on the rice genotypes planted on the different rice fields. The study also shows that quantitative analysis of populations through geometric morphometric analysis of shape variations is helpful in understanding the nature of variability among populations.
Keywords: Hindwings; Geometric morphometrics; S.coarctata